Geochemical and gas bearing characteristics of the marine-continental transitional Longtan shales in southern Sichuan, China - Chen, Yana; Pei, Xiangyang; Zhang, Jizhen; Wang, Nan; Han, Denglin; Wang, Juan; Xiao, Xiao; Wang, Jianguo (Frontiers in Earth Science, 2023)
Marine-continental transitional shale, as an important shale type, gains less attention than marine and continental shale, which restricts the exploration and development process of marine-continental transitional shale gas. In this study, the Upper Permian Longtan Formation shale in the southern Sichuan Basin was taken as the research object, and the organic matter development characteristics, hydrocarbon generation ability, mineral composition, physical properties, and gas bearing characteristics of the Longtan Formation shale were systematically analyzed. In addition, the effects of organic matter abundance, maturity, and mineral components on shale gas adsorption capacity have been discussed in detail. The results show that the abundance of organic matter in the marine continental transitional shale of the Longtan Formation in southern Sichuan varies greatly, with the TOC value of the vast majority of shale being greater than 2.0%, with the carbon shale (TOC>12%) accounting for about 5%. The main type of organic matter is Type III, with part of Type II2. The maturity of organic matter is in the stage of high maturity to over maturity, which is conducive to the generation of dry gas. There is a good positive linear correlation between the reflectance of vitrinite (Ro) and the maximum thermal decomposition peak temperature (Tmax) of rock. The higher the abundance of organic matter, the greater the hydrocarbon generation potential of shale, and the carbonaceous shale shows good shale gas generation potential. The shale of the Longtan Formation is rich in clay minerals, with the highest content of the illite/smectite mixed layer. The abundance and maturity of organic matter jointlypromote the enrichment of Longtan shale gas. The enrichment of clay minerals is beneficial to shale gas adsorption, but poses a challenge to production fracturing.